EU STRATEGIES AND POLICIES FOR NEIGHBOURING STATES: HOW RELIABLE IS A COOPERATION WITH THE RUSSIAN FEDERATION? - Ambruș, Georgiana-Ștefania (EURINT (Iași), 2021)
Russia and the need to secure the eastern flank have been mentioned over time, and the subject has grown in complexity along with the development of international policies and, at the same time, Moscow's intentions to maintain its presence outside its borders. The recent military mobilizations on the border with Ukraine, as well as the Russian interference in the internal policies of the ex-communist states, significantly increase the need of the EU and NATO to bring new instruments of action in the face of the Russian threat, especially on the eastern flank. So, throughout the article we will see Russia's lines of action towards the Eastern Neighborhood and the European Union's rhetoric about them.